STUDIES ON FLORAL BIOLOGY AND BREEDING BEHAVIOUR OF VIOUR OF SWEET ORANGE [ SWEET ORANGE [CITRUS SINENSIS CITRUS SINENSIS CITRUS SINENSIS (L.) OSBECK.] - ANIL KUMAR GODARA, R. B. KUMATKAR,; SHARMA, VIKAS KUMAR (The Bioscan, 2016)
In sweet orange flowering takes place only once in year i.e. February–March under North Indian conditions. The duration of floral bud development was 19-23 days in different cultivars and Jaffa was earliest to start flowering. The duration of flowering was 20-23 days in the cultivars. These cultivars came to full bloom in first week of March. Two type of inflorescence were observed i.e. leafy and leafless. The flowers were born on current season’s growth in the axils of leaves either solitary or in cymes. Flower structure observed in sweet orange with five sepals, five petals and twenty stamens with superior ovary. The maximum opening of flowers and dehiscence of anthers took place in morning hours (10.00 A.M. to 12.00 noon) in all the cultivars. Stigma became receptive just after anthesis and remained receptive till 72 hours for pollination in all the cultivars. The maximum receptivity was recorded on the day of anthesis. The highest fruit set was recorded in cultivar Jaffa under open pollination (32.84%) followed by self-pollination (29.81%). From the results obtained, it showed that sweet orange cv. Jaffa followed by Pineapple proved to be best with respect to flowering and fruit set.